Evidence In Sexual Violence Crime Cases - Made Pasek Swardhyana, Gde; Irawan, Aris (CV. Inara, 2022)
The focus of this research is related to the emergency phenomenon of sexual violence in Indonesia which is currently the world's concern. Evidence of criminal acts of sexual violence is often not revealed because it is constrained by the narrow evidence in the regulations for combating sexual violence crimes in Indonesia. The presence of Law Number 12 of 2022 concerning the Crime of Sexual Violence has become a breath of fresh air in the disclosure of cases of sexual violence in Indonesia, which is among the highest in Southeast Asia. To answer the objectives of this research, the type of research used is normative legal research with a statutory approach, a conceptual approach and a comparative approach, especially examining legal provisions related to evidence in sexual violence crimes in Indonesia. In the perspective of the ratio decidendi in criminal justice, it is related to the importance of evidence in overcoming this sexual violence crime in Indonesia. From the results of the study, it was found that there were several additional evidences in the Non-Criminal Act on Sexual Violence as a new regulation in dealing with sexual violence in Indonesia, including the recognition of victim statements, statements by psychologists and/or psychiatrists, electronic evidence, this is progress in the process. justice for sexual violence crimes in Indonesia by also including some additional new evidence, including psychiatrists' statements which are very helpful in disclosing cases of criminal acts of sexual violence in Indonesia which are increasingly showing alarming numbers. Entering silent evidence or evidence as a tool The evidence in the regulation of this new law provides another perspective in overcoming the crime of sexual violence in Indonesia which is difficult to uncover due to cultural factors and negative stigma towards victims of sexual violence.